On-Demand Isn’t Built in a Day: Promotional Rhetoric and the Challenges of Net ix’s Arrival in Italy (Cinéma & Cie. Film and Media Studies Journal, 2017)
In the months surrounding Net ix’s arrival on the Italian market, different media outlets presented the platform not only as revolutionary, a game-changer, but also as a threat for established broadcasters. After a long wait, with hype fanned by the news coming from the US, the launch in many other European markets, and the strengths of the rst branded productions, Italian TV audiences have also been able to access Net ix’s library and original series, since 22 October 2015. On the one hand, Net ix has reaped the results of its effort to establish a long-term promotional discourse in Italy. On the other, however, Net ix’s late appearance was also couched in the context of a complex media scenario and an already established national on-demand market. A rhetoric of disintermediation has been carefully constructed at the exact moment when a powerful global intermediary was entering the Italian market, masking its (future, intended) gatekeeping role. Adopting a media-industry and production-studies approach, this essay reconstructs Net ix’s arrival in the Italian landscape, focusing on the promotional discourse and its rhetoric, and on the reactions from the press, to give a deeper, more nuanced view of the phenomenon in the national media arena.